Comparative analysis of sexual dimorphism in ultrastructure of sensilla on antennae, frons, and compound eyes of Azpeytia shirakii Hurkmans (Diptera: Syrphidae) - Bin Mao; Yu-Hui Cong; Ming-Hui Wang; Han-Rui Ren; Yun-Li Xiao (Zoomorphology, 2025)

The potential of anthraquinone-2-sulfonate (AQS) for “shell breaking” of iron-coated denitrification granular sludge - Xin-Rui Zhang; Zhi-Han Xi; Zi-Jun Yan; Xin-Tao Liu; Ying Wang; Run-Mei Li; Zi-Yue Li; Ke-Yu Wu; Ren-Cun Jin; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Management, 2025)

Quaternary Glaciation Accelerates Speciation in Aquatic Snakes Through Recent Bottlenecks - Jin‐Long Ren; Rui‐Han Li; Ru‐Wan Jia; Zhi‐Tong Lyu; Chaochao Yan; Dechun Jiang; Ying‐Yong Wang; Jia‐Tang Li (Molecular Ecology, 2025)
Climatic fluctuations during glacial periods have profoundly shaped the demographic history and gene flow dynamics of many taxa. This study integrated high‐throughput sequencing of 67 individuals with comprehensive genomic analyses to investigate biogeographic patterns, genetic divergence and demographic trajectories in the Opisthotropis latouchii species complex, a group of mountain stream snakes distributed across Central China. Our analyses revealed substantial genetic divergence, identifying four distinct lineages, each confined to one of the four major mountain ranges in Central China, including one previously unrecognised species. These lineages exhibited distinct demographic signatures, with population bottlenecks occurring during Quaternary glaciations. Initial isolation in the glacial refugia of the southern regions of these mountains during the Late Pliocene was followed by postglacial expansions along a northward trajectory, with further divergence along a latitudinal gradient associated with mountain distribution. Notably, the mountain ranges of Central China acted as critical refugia during glacial periods, promoting rapid speciation, and as dispersal corridors during interglacial periods, facilitating range expansion and enabling recent gene flow. These findings highlight the profound impact of Quaternary climatic oscillations on genetic structure, demographic history and gene flow patterns of these endemic taxa.

Synergistic enhancement of agricultural waste biochar in Cr(III)/methylene blue co-pollutant systems: Structure regulation and co-adsorption mechanistic insights - Binqiao Ren; Xue Han; Yu Jin; Yuying Zhang; Xiaoxiao Song; Luyang Zhao; Rui Liu (Journal of Environmental Chemical Engineering, 2025)

Engineering a recombinant VP2-Based neutralizing epitope vaccine candidate against canine parvovirus: a preliminary immunogenicity assessment - Qing Wu; Yuhan Jin; Weiyue Cao; Zeheng Ren; Xinyu Li; Zhitong Li; Jiachi Han; Chunxu Shi; Rui Gao; Min Yan; Shengrui Zhu; Wenpeng Guan; et al. (Veterinary Research Communications, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

An alternative ignition agent concept based on ionic integrated energetic oxidant - Xiaoxia Li; Peng Ren; Rui Wu; Yu Wang; Peng Deng; Kehua Han; Yu Shang; Shaoli Chen; Weixiong Zhang (Chemical Engineering Journal, 2025)

Role of a noval amadori rearrangement product: N- (1-deoxy-D-fructos-1-yl) -γ-aminobutyric acid in changing the taste of Huangjiu - Gang Han; Zhilei Zhou; Rui Chang; Qingxi Ren; Zhongwei Ji; Xibiao Xu; Yuezheng Xu; Jian Mao (Food Bioscience, 2025)